Correlation of ultrasonic velocity slowness with uniaxial compressive strength of schists in Malaysia - Goh Thian Lai, Abdul Ghani Rafek, Ailie Sofyiana Serasa, Norbert, . (2015)
The uniaxial compressive strength (UCS) of rock material is one of the important mechanical parameters widely used for design, analysis and modeling in geotechnical engineering. Determination of UCS is destructive, expensive and time consuming. Recent trends have shown that ultrasonic velocity testing is a viable option for the prediction of UCS, considering that ultrasonic velocity testing is non-destructive, relatively inexpensive, fast and easy to conduct.